The economics of water management in Southern Africa an environmental accounting approach - Lange, Glenn-Marie.; Hassan, Rashid M.; Arntzen, Jaap.; Crawford, Jack.; Mungatana, Eric.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2006)
This book presents a valuable new tool for water management--water resource accounting--which significantly advances the economic analysis of water. Water resource accounts integrate detailed information about water supply and use with national income accounts to show the economic use of water, costs and tariffs paid, and the economic value of water for different economic uses.
pt. 1. Water accounts -- pt. 2. Major regional water policy issues -- pt. 3. Economic valuation of water.
Includes bibliographical references and index.
Keywords: Water-supply -- Africa, Southern -- Management; Water-supply -- Africa, Southern -- Accounting; Water resources development -- Environmental aspects -- Africa, Southern; Environmental auditing -- Africa, Southern; Electronic books